FOR BEFORE THE INITIAL WORD: A POETIC BIO-GRAPHY - Balestero, Jorge Augusto (Centro Univ Uniabeu, 2015)
Within the limits of a phenomenological approach, this study proposes examining a possible empathetic gesture in poetic review at the book Lar, by Armando Freitas Filho. As performance of fictional memory, it is proposed that poetry supposedly biographical outlines a set of relations and differences between individual search path for poetry and the legacy of achievements left by a long poetic tradition. Analyzes some iconic poems book with view to determining whether such a proposal.
Keywords: Genesis; empathy; poetic inter-subjectivity